Tuberculosis of the calcaneum masquerading as Haglund's deformity: a rare case and brief literature review. (24th May 2013) - Gillott, Elizabeth; Ray, Pinak
Abstract : An Asian man presented to the Foot and Ankle Clinic with a 5-month history of right ankle pain of gradual onset. He had a non-fluctuant swelling around the Achilles tendon insertion with a tender palpable lump. Radiograph demonstrated Haglund's deformity and also possible calcification at the attachment of the Achilles tendon for which he had an injection of a local anaesthetic and a steroid to treat the insertional Achilles tendinitis. A few months later, he developed acute anorexia, abdominal distension secondary to ascites and groin lymphadenopathy. Histology of the lymph node biopsy revealed granulomatous lymphadenitis consistent with tuberculosis (TB) and started on quadruple agent anti-TB treatment. The sample was not cultured. He developed constant ooze from his groin lymph node biopsy site and also fluctuance around the Achilles tendon and heel. Pus from the heel stained positive for auramine indicating TB calcaneum with subsequent culture for acid fast bacilli (AFB) confirming diagnosis of TB calcaneum.